Desirable and undesirable difficulties: Influences of variability, training schedule, and aptitude on nonnative phonetic learning - Fuhrmeister, Pamela; Myers, Emily B. (Attention, perception & psychophysics, 2020)
Adult listeners often struggle to learn to distinguish speech sounds not present in their native language. High-variability training sets (i.e., stimuli produced by multiple talkers or stimuli that occur in diverse phonological contexts) often result in better retention of the learned information, as well as increased generalization to new instances. However, high-variability training is also more challenging, and not every listener can take advantage of this kind of training. An open question is how variability should be introduced to the learner in order to capitalize on the benefits of such training without derailing the training process. The current study manipulated phonological variability as native English speakers learned a difficult nonnative (Hindi) contrast by presenting the nonnative contrast in the context of two different vowels (/i/ and /u/). In a between-subjects design, variability was manipulated during training and during test. Participants were trained in the evening hours and returned the next morning for reassessment to test for retention of the speech sounds. We found that blocked training was superior to interleaved training for both learning and retention, but for learners in the interleaved training group, higher pretraining aptitude predicted better identification performance. Further, pretraining discrimination aptitude positively predicted changes in phonetic discrimination after a period of off-line consolidation, regardless of the training manipulation. These findings add to a growing literature suggesting that variability may come at a cost in phonetic learning and that aptitude can affect both learning and retention of nonnative speech sounds.